2013
DOI: 10.4172/2324-9005.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Related Stigma: What we Know and the Way Forward

Abstract: Aims To conduct a systematic review of the literature investigating the relationship between stigma experienced by individuals who use drugs. Methods We conducted an online literature search and identified articles related to stigma among individuals who use drugs. Studies evaluating associations between stigma and socio-demographic variables and if applicable clinical and substance use variables are presented. In addition, recommendations for future research are provided. Results We identified 26 articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 53 publications
3
124
2
Order By: Relevance
“…Results on the predictive value of further demographic measures on stigma are also inconsistent [24]. While lower educational level was associated with higher stigma in patients with depression [55], higher education was found to be a risk factor for self-stigma in patients with SUD [56].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Results on the predictive value of further demographic measures on stigma are also inconsistent [24]. While lower educational level was associated with higher stigma in patients with depression [55], higher education was found to be a risk factor for self-stigma in patients with SUD [56].…”
Section: Discussionmentioning
confidence: 95%
“…Schomerus et al [7] found that among individuals who drink alcohol, self-stigma was negatively correlated with self-efficacy to refuse drinking. Results regarding sociodemographic variables are inconsistent, presumably due to the variance of the investigated samples and stigma types [24]. However, higher perceived stigma towards people who use alcohol seems to be associated with a lower level of education.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[22] Such stigma is also fueled from the common misconceptions that surround groups such as individuals with SUDs. [23] As the Surgeon General points out, health professionals may attribute the impaired decision making of individuals with SUDs as a character flaw.…”
Section: Reducing the Impact Of Cultural Models That Breed Stigmamentioning
confidence: 99%
“…In fact, substance use is, compared to other conditions, one of the most stigmatized [3,4]. It is 'strongly moralized' [5] and often seen as a condition over which one has personal control [6]. Consequently, substance users are frequently viewed as weak and immoral people that can be held personally responsible for both the onset and continuation of their substance use dependence [3,7,8].…”
Section: Introductionmentioning
confidence: 99%